FORMALIZING PRODUCT COST DISTORTION: The Impact of Volume-Related Allocation Bases on Cost Information - Jermias, Johnny (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
The purpose o f this study is to formally analyze product cost distortions resulting from the process of allocating costs to products based on Activity-Based Costing (ABC) and the conventional product costing systems. The model developed in this paper rigorously shows the impact of treating costs that are not volume related as if they are. The model demonstrates that the source of product cost distortion is the difference between the proportion of driver used by each product in ABC and the proportion of the base used by the same product in the conventional costing systems. The difference arises because the conventional costing systems ignore the existence of batch-related and product-related costs. The model predicts a positive association between volume and size diversity with product cost distortions. When interaction between volume and size diversity exists, the distortion is either mitigated or exacerbated. The magnitude of the distortion is jointly determined by the size of the differences and the size of the total indirect costs.